2016
DOI: 10.1021/jacs.6b02701
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Copper(II) Photoinduced Polymerization of Acrylates: Low Copper Concentration and the Importance of Sodium Halide Salts

Abstract: Photoinduced metal mediated radical polymerization is a rapidly developing technique which allows for the synthesis of macromolecules with defined molecular weight and narrow molecular weight distributions, although typically exhibiting significant limitations in aqueous media. Herein we demonstrate that the presence of alkali metal halide salts in conjunction with low copper concentration and UV irradiation, allows for the controlled polymerization of water soluble acrylates in aqueous media, yielding narrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 65 publications
1
72
0
Order By: Relevance
“…60%) and extensively purify the macroinitiator product prior to performing a chain extension experiment which is a waste of materials and time consuming limiting commercial exploitation and attractiveness. In order to circumvent this, a number of different "variations" of ATRP and SET-LRP have recently been developed, including use of free radical initiators (initiators for continuous activator regeneration (ICAR) ATRP) 20 , reducing agents (activators regenerated by electron transfer (ARGET) and AGET ATRP) 21,22 , electrochemical (eATRP) 23 and light stimuli (light ATRP), [24][25][26][27][28][29][30] as well as Cu(0)-wire and Cu(0) particle mediated processes. 31,32 The latter two approaches have demonstrated high end group fidelity even at near-quantitative conversions as exemplified by the in situ synthesis of multiblock copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…60%) and extensively purify the macroinitiator product prior to performing a chain extension experiment which is a waste of materials and time consuming limiting commercial exploitation and attractiveness. In order to circumvent this, a number of different "variations" of ATRP and SET-LRP have recently been developed, including use of free radical initiators (initiators for continuous activator regeneration (ICAR) ATRP) 20 , reducing agents (activators regenerated by electron transfer (ARGET) and AGET ATRP) 21,22 , electrochemical (eATRP) 23 and light stimuli (light ATRP), [24][25][26][27][28][29][30] as well as Cu(0)-wire and Cu(0) particle mediated processes. 31,32 The latter two approaches have demonstrated high end group fidelity even at near-quantitative conversions as exemplified by the in situ synthesis of multiblock copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…To polymerize the new diTBA monomer, our attention was directed to recent advances in photo‐induced controlled radical polymerization . A recent report by Haddleton and coworkers demonstrated that tert ‐butyl acrylate could be polymerized to very high conversions while retaining excellent end group fidelity (>99%) using catalytic Cu II Br 2 and an aliphatic amine ligand, Me 6 ‐Tren, in the presence of UV ( λ max ≈ 360nm) light .…”
Section: Resultsmentioning
confidence: 99%
“…Re‐initiation with sequential addition of alternative monomers can lead to the formation of multi‐block copolymers with complex compositions in which the side chain functionality is not perfectly, but discretely distributed throughout each polymer chain . The most recent advances in Cu‐mediated RDRP have centred on retaining this control over polymerisation in aqueous and biologically relevent media and using external stimuli to control the activation‐deactivation equilibrium (Figure ) …”
Section: ‘Precision’ Polymerisation Using Aqueous Rdrpmentioning
confidence: 99%